AN UNUSUAL PATHOGEN CAUSING NATIVE VALVE ENDOCARDITIS - Hussain, Aneela; Nasir, Nosheen; Jamil, Bushra (Journal of Ayub Medical College Abbottabad, 2016)
We present the case of a gentleman who was being evaluated for restrictive lung disease and was incidentally found to have mitral valve stenosis on an HRCT. During the surgical procedure for valve replacement, he was found to have an abscess around the native mitral valve which was drained. Pus from the abscess as well as the valve tissue grew Propionibacterium acnes after holding the cultures long. The patient was treated with IV ceftriaxone with good response to therapy. While Propionibacterium acnes is known to cause prosthetic valve infections there are rare case reports with native valves. This is the first case to be reported from our country. Keywords: Endocarditis, Propionibacterium acnes, Valvular disease, Mitral valve replacement